An Efficient FEC Allocation Algorithm for Unequal Error Protection of Wireless Video Transmission - Chang, Yoong Choon; Lee, Sze Wei; Komiya, Ryoichi (2009)
Transmission of compressed video over wireless channels remains a challenging task due to the inherent high bit error rate (BER) and channel quality fluctuation of a typical wireless channel. An improved wireless video transmission scheme is proposed in this paper. First, an enhanced video error propagation model, namely expected number of macroblocks error propagation (ENMEP), is proposed. A new unequal error protection (UEP) scheme which takes into consideration the non-uniformly distributed importance of frames in a group of pictures (GOP) and macroblocks in a video frame is also proposed in this paper. Finally, an efficient forward error correction (FEC) allocation algorithm for our UEP scheme is proposed by making use of our ENMEP video error propagation model. Simulation results show that our proposed UEP scheme using efficient FEC allocation algorithm outperforms the classical equal error protection (EEP) scheme and also the previous UEP scheme.